Application of computer-controlled, real-time TV single-object tracking in behavioural biology and rehabilitation medicine - Kaminsky, Y; Krekule, I (Physiological research, 1997)
A PC-based system with TV input for automatic tracking of a single and contrast object in 2D in a homogeneous and stationary environment has been developed and applied to Morris water maze experiments. Further development of the system aimed at broader support of experiments, reduction of requirements on the stationarity and homogeneity of the scene background and on multiple-object tracking is discussed. The computer control of active light markers of the tracked object applicable to multiple-objects tracking in a time-sharing regime is also mentioned in the conclusion. The latter extension of the system can be applied to kinematic studies in biomechanics, sport and rehabilitation medicine.
Keywords: Computers; Maze Learning; Animals, Laboratory; Rehabilitation; Behavior, Animal; Software; chování zvířat; bludiště - učení; software; televize; Animals; laboratorní zvířata; audiovizuální záznam; rehabilitace; Video Recording; zvířata; počítače; Television